Immersive Journalism, a “New Frontier” of Information Experience? - Toursel, Angelina; Philippe, Useille (Brazilian journalism research, 2019)
In this paper, we study how journalists use Virtual Reality (VR) technology which started off as a form of entertainment to produce new forms of interactive narratives. The paper presents the context of the emergence of this new form related to news reportings and to VR technology in the light of media history and visual culture. One of the main implications of immersive journalism consists in putting the viewer in an environment she/he can explore. It is often described as a sense of presence. We will focus mainly on the VR reporting The Fight for Falluja (2016) by Ben C. Solomon (The New York Times) to study this effect of presence, which is usually associated with entertainment, which becomes a distant presence here, modulated by the writing of the reporting, or by the VR narrative. Neste paper, analisamos como os jornalistas usam a tecnologia da Realidade Virtual (RV), inicialmente introduzida como uma forma de entretenimento para produzir novas formas de narrativas interativas. O paper apresenta o contexto de emergência dessa forma de relato da reportagem jornalística e da realidade virtual, com base na história da mídia e da cultura visual. Uma das principais implicações do jornalismo imersivo consiste em colocar a/o usuária/o em um ambiente em que ela/ele possa explorar. Isso é frequentemente descrito como sentido de presença. Centralizaremos o nosso interesse particularmente na reportagem RV “The Fight for Falluja” (2016) por Ben C. Solomon (The New York Times) com o objetivo de estudar esse efeito de presença, usualmente associado ao entretenimento e que se torna uma presença próxima, modulada pela redação reportagem, ou pela narrativa RV. En este artículo, estudiamos cómo los periodistas utilizan la tecnología de Realidad Virtual (RV), que comenzó como una forma de entretenimiento para producir nuevas formas de narrativas interactivas. El documento presenta el contexto de la aparición de esta nueva forma relacionada con la información periodística y la tecnología de la RV a la luz de la historia de los medios de comunicación y la cultura visual. Una de las principales implicaciones del periodismo inmersivo consiste en poner al espectador en un entorno que pueda explorar. A menudo se describe como un sentido de presencia. Nos centraremos principalmente en el reportaje de RV The Fight for Falluja (2016) de Ben C. Solomon (The New York Times) para estudiar este efecto de la presencia, que suele asociarse con el entretenimiento, que se convierte en una presencia distante aquí, modulada por la escritura del reportaje, o por la narrativa de la RV.